2009
DOI: 10.4081/814
|View full text |Cite
|
Sign up to set email alerts
|

60KDa chaperonin (HSP60) is over-expressed during colorectal carcinogenesis

Abstract: The aim of the present study was to evaluate the expression of the heat shock protein 60 (HSP60), a mitochondrial matrix-associated protein belonging to the chaperonin family, in colorectal adenomas and cancers, comparing them to normal colonic tissues and hyperplastic polyps. We performed both immunohistochemistry and Western blot analysis for HSP60. Immunohistochemistry resulted positive in all tubular adenomas and infiltrating adenocarcinomas. By contrast, normal tissues and hyperplastic polyps were negativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
67
1
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(74 citation statements)
references
References 16 publications
(10 reference statements)
5
67
1
1
Order By: Relevance
“…22,23 As mentioned above, more recently we studied a series of patients with IBDFa condition considered high-risk for cancer developmentFand we found increased levels of Hsp60 in both Crohn disease and UC, postulating that this protein could be implicated in their pathogenesis by triggering and/or maintaining inflammation. 5 We found that the increased levels of the chaperonins were associated with an increase in inflammatory cells in both pathologies by comparison with normal mucosa.…”
mentioning
confidence: 73%
“…22,23 As mentioned above, more recently we studied a series of patients with IBDFa condition considered high-risk for cancer developmentFand we found increased levels of Hsp60 in both Crohn disease and UC, postulating that this protein could be implicated in their pathogenesis by triggering and/or maintaining inflammation. 5 We found that the increased levels of the chaperonins were associated with an increase in inflammatory cells in both pathologies by comparison with normal mucosa.…”
mentioning
confidence: 73%
“…[1][2][3] We study these chaperones that work as a rule in conjunction with one another, 4,5 and we have found that their expression varies with distinctive patterns in different malignancies. They are overexpressed in colorectal, exocervical and prostate carcinogenesis, [6][7][8][9] and colorectal cancer progression, 10 but are downregulated during bronchial carcinogenesis. 11 In view of these reports and findings we would like to call attention to the potential of Hsp60 and Hsp10 in cancer therapy.…”
Section: Introductionmentioning
confidence: 99%
“…(1) human Hsp60 was found overexpressed or downregulated in tumors; [6][7][8][9][10][11] (2) the chaperone would specifically interact with antigenpresenting cells (APC) and boost secretion of pro-inflammatory cytokines by macrophages and dendritic cells, promoting maturation of dendritic cells; 18 (3) highly purified human Hsp60 triggered human T lymphocyte proliferation in vitro. 19 The response to Hsp60 seemingly was driven by the naive CD45RA+ RO-T cell subset or cord-blood cells.…”
Section: Introductionmentioning
confidence: 99%
“…HSP10 is encoded by a nuclear gene; the newly translated protein is transported into the mitochondria (18), and HSP10 is mostly localized in the mitochondrial matrix (11). In contrast, increased content of HSP10 has been observed in the cytosol of some cancer cells (9,10), although the mechanisms by which HSP10 is retained in the cytoplasm in these circumstances are not fully understood (11).…”
mentioning
confidence: 96%